2010
DOI: 10.1246/cl.2010.1008
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated Polymer Micelle-based Nitric Oxide (NO) Photodonor with NO-mediated Antitumor Activity

Abstract: PEGylated polymer micelles containing 4-nitro-3-trifluoromethylphenyl units within the core moiety were prepared, and their phototriggered nitric oxide (NO)-generating ability was confirmed by electron spin resonance (ESR) spin-trapping and the Griess method. These micelles were found to be capable of delivering exogenous NO into tumor cells in a photocontrolled manner and showed an NO-mediated antitumor effect, indicating the usability of this molecular system in NO-based tumor therapy.Nitric oxide (NO) is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Kanayama et al [115] reported that PEGylated polymer micelles may be capable of delivering exogenous NO to tumor cells in a photocontrolled manner, resulting in an NO-mediated antitumor effect, which indicates the promise of this polymeric system in NO-based tumor therapy. Friedman et al reported that therapeutic levels of NO, in controlled and sustained manner, can be achieved by using combination of glassy matrices and hydrogels [116].…”
Section: Reviewmentioning
confidence: 99%
“…Kanayama et al [115] reported that PEGylated polymer micelles may be capable of delivering exogenous NO to tumor cells in a photocontrolled manner, resulting in an NO-mediated antitumor effect, which indicates the promise of this polymeric system in NO-based tumor therapy. Friedman et al reported that therapeutic levels of NO, in controlled and sustained manner, can be achieved by using combination of glassy matrices and hydrogels [116].…”
Section: Reviewmentioning
confidence: 99%
“…To improve the NO payload and stability, achieve targeted NO delivery through multi-functionalization and elongate NO releasing lifetime, many different scaffolds have been used as NO-releasing or NO-generating vehicles. These include micelles, 138,190,191 microbubbles, 192 proteins, 193197 liposomes, 126,198 inorganic nanoparticles (such as silica, 70,199203 gold, 204,205 microparticles, 198,206 zeolites, 207,208 ), metal-organic frameworks (MOFs), 209212 dendrimers, 71,213,214 xerogels, 215217 electrospun fibers, 88,100,218 natural polymers (chitosan, 8587,219221 gelatin, 222 etc. ), and other organic polymers (polymethacrylate, 223 polyester, 224,225 polydimethylsiloxane (PDMS), 226 polysaccharides, 227,228 hydrogel, 178,179,229,230 PVA, 49,231,232 polyurethanes, 161,162,233,234 and PVC 154 ).…”
Section: Polymer-based Strategies For No Deliverymentioning
confidence: 99%
“…NO is considered to be a promising ideal drug that not only exerts therapeutic effects, but also minimizes side effects because of its endogenous presence in vivo and rapid transformation into innocuous ions within six seconds or less after its action, as contrasted with other chemotherapeutics and nucleotide drugs [2734]. Accordingly, numerous NO-donors defined as NO-releasing functional moieties or small molecule drugs have been developed and applied to biomaterials for evaluation as therapeutic modalities [2938]. As the complicated functions of NO are highly dependent on its concentration and duration [28], NO delivery systems that can deliver NO donors to the target sites and control the NO release are prerequisite to realize the full potential of NO [34].…”
Section: Introductionmentioning
confidence: 99%
“…Direct killing of cancer cells can be achieved with high concentration of NO (µM-mM) [3538], however, its practical applications are limited due to the poor bioavailability of NO-donors with low NO capacity and instability during storage and systemic circulation. On the other hand, broad ranges of NO concentrations have shown chemosensitizing effect to reverse MDR, which has recently inspired researchers to develop combined NO and drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%